2017
DOI: 10.1038/cr.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Viral effector protein manipulates host hormone signaling to attract insect vectors

Abstract: Some plant and animal pathogens can manipulate their hosts to cause them to release odors that are attractive to the pathogens' arthropod vectors. However, the molecular mechanism underlying this process is largely unexplored, and the specific effectors the pathogens employ as well as the pathways within the hosts they target are currently unknown. Here we reveal that the aphid-borne cucumber mosaic virus (CMV) employs its 2b protein, a well-characterized viral suppressor of host RNA interference (VSR), to tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 50 publications
(91 reference statements)
3
99
0
2
Order By: Relevance
“…HIS-JAZb and HIS-JAZi degradation assays were performed as described (85). Flowers in the early floral stage of each genotype were used for crude protein extraction.…”
Section: Methodsmentioning
confidence: 99%
“…HIS-JAZb and HIS-JAZi degradation assays were performed as described (85). Flowers in the early floral stage of each genotype were used for crude protein extraction.…”
Section: Methodsmentioning
confidence: 99%
“…However, it did not change the attraction of M. persicae as a virus vector, but increased its feeding time on plant. By contrast, protein 2b increased immigration of M. persicae to infected Arabidopsis plants, but decreased its settling on virus-infected plants (Wu et al, 2017). Groen et al (2017) proposed that nonpersistent virus has two transmission types in different plant hosts.…”
Section: Cucumber Mosaic Virus and Barley Yellow Dwarf Luteovirus (Vimentioning
confidence: 99%
“…JA is the main hormone that regulates volatile biosynthesis in plants (Arimura & Pearse, 2017). Therefore, invaders use several strategies to control JA signaling and subsequent volatile emissions in plants (Krumm et al, 1995;Wu et al, 2017). JASMONATE ZIM DOMAIN (JAZ) is a key target of microbes in their effort to induce or suppress JA-dependent volatile biosynthesis.…”
Section: Microbe-induced Signaling Cascades Conciliate Plant Volatilementioning
confidence: 99%
See 1 more Smart Citation
“…The rationale is that better insect survival will increase the number of vectors loaded with virus, thus promoting virus transmission. One example of a pathogen effector is CMV protein 2b that tampers with jasmonic acid signaling (Lewsey et al, 2010) to possibly promote aphid infestation and transmission (Ziebell et al, 2011;Wu et al, 2017). In another example, Casteel et al (2014) demonstrated that TuMV infection suppresses callose deposition and increases aphid fecundity on tobacco and Arabidopsis plants.…”
Section: Plant Defense-related Pathways Involved In Virus Transmissionmentioning
confidence: 99%